Therapeutic potential of phytocompounds of Bacopa monnieri (L.) Wettst (literature review) - O.O. Nikitina; D.S. Tsyba (Medičnì Perspektivi, 2024)
The aim of the work was to evaluate the pharmacological effects and therapeutic potential of individual compounds and extracts of B. monnieri based on the analysis of data from scientific periodicals regarding chemical composition and biological action. Theoretically significant were the studies of the materials of the scientific-metric database PubMed and Google Scholar over the last five years regarding the chemical composition and biological action of extracts based on B. monnieri and their individual components. The search query was carried out by the Latin name of the plant, with the exception of publications related to botanical research. In separate PubChem searches, names of individual phytocompounds were used to establish structure and distribution in plants. The SuperPred web server was used to predict therapeutic potential. The authors analyzed the chemical composition of the extracts, presented the structural and pharmacological characteristics of bacosides and their aglycones: bacosin and juubogenin, cucurbitacin E, loliolide, betulinic and asiatic acids and the flavonoid oroxindin. The mechanism of action of bacoside on β-amyloid is characterized and illustrated. Using machine learning, the prospects for using the main compounds of bacopa to create drugs were calculated taking into account the ATC classification, their biological effects and alternative plant sources were given. Experimental animal studies of whole aqueous or ethanolic extracts of B. monnieri have been found to support a cognitive enhancement effect. The extract was not toxic to humans. Numerous clinical trials show the effectiveness of the use of extracts in the treatment of anhedonia, depression, Alzheimer's disease, Parkinson's disease, dementia and hyperactivity. An analysis of clinical studies in Ukraine shows that drugs based on B. monnieri can be used in the complex treatment of cognitive impairment associated with dyscirculatory encephalopathy in adults and perinatal CNS damage in children. Considering the amphiphilicity of bacosides and the non-toxicity of extracts, they can be involved in the development of various dosage forms with a wide range of therapeutic applications. Further study of the pharmacological action of B. monnieri and the development of drug technology for solid and liquid dosage forms based on it are promising.